“Methods in Teaching English as a Foreign Language” - Oyaque Vasquez, Jessika Alejandra (2024)
Currently, English serves as the universal means of communication across nations. Despite, the fact that the Ministry of Education has incorporated English as an important subject from an early stage, the list emitted in 2023 from Education First (EF) positions Ecuador in 80th position between the countries with the lowest proficiency of English around the word. in the curriculum. This may be attributed to the methodology used by English teachers in their classrooms. Therefore, this quantitative descriptive research aims to analyze the use of traditional teaching methods in English teaching as a foreign language in educative institutions from the urban sector of Latacunga. The data was collected by applying a survey to eighty-two English teachers from different educational institutions in the city of Latacunga. Data was analyzed by using the SPSS (Statistical Package for the Social Sciences) calculating the mean of each item and of the whole method to determine the frequency of using the methods mentioned above. The principal findings were that English teachers tend to highly employ activities, strategies and techniques that correspond to traditional teaching methods in EFL classrooms. The results revealed that traditional methods such as Total Physical Response and Silent way were the most common methods used at teaching. The findings evidenced the strong presence of traditional teaching methods in EFL classrooms nowadays. Concluding that the teacher praxis is not limited to use a specific method, opposite from this, it showed that